Penolakan Pasien Dalam Keadaan Darurat Karena Belum Divaksin - Nandito Joi Sangadji; Hadibah Zachra Wadjo; Carolina Tuhumury (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Criminal liability arises when the damage caused by the negligence of the hospital's medical staff meets three factors: The three factors are the presence or absence of negligence, wrongdoing, and other relevant sanctions. In addition, under the criminal justice system, if a company commits a crime, its owner can be jailed or fined.Purposes of the Research: This study aims to analyze and explain the refusal of patients in an emergency situation because they have not been vaccinated against the Health Law Number 36 of 2009 and to analyze and explain the legal policy mechanism taken for patients in an emergency situation because they have not been vaccinated who are referred to the hospital.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The refusal of patients in an emergency situation because they have not been vaccinated is contrary to the Health Law No. 36 of 2009. In which the Law of the Republic of Indonesia No. 36 of 2009 concerning Health has regulated the refusal of health services by hospitals. The legal policy mechanism that is taken for emergency patients because they have not been vaccinated is that they still pay attention to the existing legal rules for both patients and for the hospital, by prioritizing patient safety first, all patients are entitled to outpatient medical services, inpatient care, or emergency department at a health facility. This is regulated in the Law of the Republic of Indonesia number 29 of 2004 concerning medical practice, Law of the Republic of Indonesia number 36 of 2009 concerning health. The refusal to take care of the patient's health is ignored by medical institutions, because it can worsen the patient's condition.